The plot [compact disc, unabridged] - Korelitz, Jean Hanff, 1961- (Macmillan Audio, 2021)
Wildly successful author Jacob Finch Bonner, who had stolen the plot of his book from a late student, fights to hide the truth from his fans and publishers, while trying to figure out who wants to destroy him.